Inverse kinematics calculation in IEC 61131-3 Structured Text: KinIn - Joseph Ramses Méndez Cam; Félix Melchor Santos López (SoftwareX, 2025)
IEC 61131-3 is a widely recognized standard in industrial programming, with its Structured Text programming language frequently employed for developing complex applications. However, there is a notable lack of comprehensive libraries for the analysis of custom mechanisms in Structured Text. To address the limitations associated with programming in IEC 61131-3, KinIn was developed as a framework implementing essential linear algebra operations and functions for inverse kinematics computation. This paper details the core components of the framework, the implemented functions, and their interconnections. The mathematical foundations of exponential coordinates used in the calculations are briefly introduced, and the framework’s utility is demonstrated through an illustrative example in the domain of heavy machinery.